The effect of controlled movement imaginary on performance in a modified 7-metre shot test of elite female handball players - Benešová, D.; Drozdová, P. (Studia Sportiva, 2024)
Movement imagery may have a favourable influence on subsequent movement performance. As a result of creating a multi-modal movement image in the mind, there are activated specific brain centres that are identical for both movement planning and actual movement action. The objective of our experiment was to find out whether a single ideomotor intervention can influence the accurate execution of a known movement skill. The research sample consisted of adult female handball players who participate in the highest Czech handball competition. We tested the movement skill in a modified 7-metre shot/throw test developed by us. The research sample was randomly divided into the experimental group and the control group. The testing involved a pretest and a posttest. It was repeated two times over the period of 2 months. The players assigned to the experimental group had significantly better performance in the posttest of both measurements in the modified test.